2017
DOI: 10.1007/s11695-017-2549-1
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Action of Surgical Interventions on Weight-Related Diseases: the Potential Role of Bile Acids

Abstract: Surgical interventions for weight-related diseases (SWRD) may have substantial and sustainable effect on weight reduction, also leading to a higher remission rate of type 2 diabetes (T2D) mellitus than any other medical treatment or lifestyle intervention. The resolution of T2D after Roux-en-Y gastric bypass (RYGB) typically occurs too quickly to be accounted for by weight loss alone, suggesting that these operations have a direct impact on glucose homeostasis. The mechanisms underlying these beneficial effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 114 publications
0
27
0
3
Order By: Relevance
“…Very recently, Mazidi et al[43] have reviewed role of bile acids its subtractions on weight loss and glycaemic control after the bariatric surgeries. They have elaborated that there is a correlation between the concentration of the total bile acid and improvements in several key metabolic parameters after bariatric surgery[43].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Very recently, Mazidi et al[43] have reviewed role of bile acids its subtractions on weight loss and glycaemic control after the bariatric surgeries. They have elaborated that there is a correlation between the concentration of the total bile acid and improvements in several key metabolic parameters after bariatric surgery[43].…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, Mazidi et al[43] have reviewed role of bile acids its subtractions on weight loss and glycaemic control after the bariatric surgeries. They have elaborated that there is a correlation between the concentration of the total bile acid and improvements in several key metabolic parameters after bariatric surgery[43]. It has been reported that there was an inverse correlation between bile acid concentrations and postprandial glucose and triglycerides, and a positive correlation with adiponectin and peak GLP-1 levels following a mixed meal test[33,44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging data have shown that BAs work as key regulator molecules of glucose and lipid metabolism that act via binding to membrane or nuclear receptors [9][10][11][12]. In severely obese individuals, strong evidence has revealed that the same organs that display impaired insulin signaling are also targeted by BA, leading to significant disruptions in BA physiology [3].…”
Section: Introductionmentioning
confidence: 99%
“…Overall, bariatric surgery by both Roux-en-Y gastric bypass (RYGB) and sleeve gastrectomy (SG), the most performed techniques at the moment, has been reported to induce important changes in BA metabolism related or nonrelated to weight loss [24,25]. These changes seem to promote metabolic health via improving insulin signaling and reducing IR, thus making, once more, BA an important therapeutic target [3,12,25]. However, while circulating BAs have been demonstrated to increase following RYGB [13,18,[26][27][28], the effect of SG on BA has shown mixed results.…”
Section: Introductionmentioning
confidence: 99%